Objective Assessment of Hyposmia in Alzheimer's Disease From Image and Behavior by Combining Pleasant Odor With Unpleasant Odor - Feng, Quanzhi; Liu, Hui; Zhang, Hui; Liu, Yi; Zhang, Huihong; Zhou, Yuying; Liu, Gang; Han, Tong (Frontiers in Neurology, 2021)
Background: Olfactory functional magnetic resonance imaging (fMRI) of responses to a pleasant odor (PO) (lavender) can objectively evaluate olfactory dysfunction in Alzheimer’s disease (AD) patients. The brain responses to a PO and unpleasant odor (UPO) were shown to differ in normal young people. Whether AD patients with olfactory dysfunction have the same brain response is not yet known. Objective: Our aim was to explore whether olfactory fMRI with both a PO and UPO can provide more information regarding olfactory impairment in AD than a PO alone. Methods: Twenty-five normal controls (NC), 26 individuals with mild cognitive impairment (MCI) and 22 AD patients underwent olfactory fMRI with lavender and pyridine odorants at three concentrations (0.10, 0.33, and 1.00%) with a 3.0T MRI scanner. Results: There were no differences in the number of activated voxels in the primary olfactory cortex (POC) between PO and UPO conditions in the NC, MCI and AD groups (SPM, paired t-test, uncorrected P<0.001, extent threshold = 70). In the right inferior frontal gyrus, orbital part (F3O), the number of activated voxels was greater with the UPO than with the PO in the NC group (SPM, paired t-test, uncorrected P<0.001, extent threshold = 70), but there were no differences in the MCI and AD groups. Regardless of PO or UPO conditions, there were significant differences in the number of activated voxels in the POC among the NC, MCI and AD groups. With increasing odor concentration, the number of activated voxels in the POC decreased in the NC group but increased in the AD group. When 0.10% UPO was presented, the NC group (21/25) showed a lower breathing amplitude and shorter inhalation time, while the AD patients (0/22) did not show such changes in breathing. Conclusions: After PO and UPO inhalation, brain activation and respiratory behavior in AD patients were significantly different than in NC patients. Therefore, olfactory fMRI using both PO and UPO stimulation, compared with PO stimulation only, can provide more objective information regarding hyposmia associated with AD based on imaging and behavior.